Implementing Authorized Economic Operator Programmers in Emerging Market Customs Administrations - Muchamad Syaika Gilang Fanani; M. Syaprin Zahidi (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study examines the implementation of the Authorized Economic Operator (AEO) program at KPPBC TMP Tanjung Perak, Indonesia’s main eastern maritime trade hub, focusing on certification procedures, compliance requirements, coordination mechanisms, and monitoring capacity constraints under the WCO SAFE Framework. Methodology: A qualitative case study was conducted using semi-structured interviews, analysis of Indonesian AEO regulations (2010–2023), and review of WCO SAFE Framework documents, with data triangulated from primary and secondary sources. Results: Findings show that Tanjung Perak Customs manages 51 AEO-certified companies under a centralized certification system. The program improves trade security and contributes significantly to foreign exchange flows (approximately IDR 78 trillion in exports and IDR 20 trillion in imports in 2020), but monitoring remains largely reactive due to limited institutional capacity. Conclusions: Indonesia’s AEO implementation reflects a hybrid governance model that delivers trade facilitation benefits but faces weaknesses in decentralized monitoring and risk-based oversight. Limitations: The study is limited to a single customs jurisdiction (2010–2023), restricting generalizability. Contribution: This research provides one of the first detailed port-level analyses of AEO governance in Indonesia, highlighting the tension between centralized certification and limited monitoring capacity, and offering implications for strengthening risk management and institutional capacity.